2004
DOI: 10.1097/00001888-200401000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Do Clerkship Directors Think Medical Students Are Prepared for the Clerkship Years?

Abstract: Almost half of clerkship directors were concerned that students do not receive adequate preparation in key competencies before starting the core clinical clerkships. Many medical schools may need to give more attention to the preclerkship preparation of students in these high-priority areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 8 publications
2
47
0
4
Order By: Relevance
“…Indeed, another medical school that included puECAs in their procedure concluded that selected students had better skills in terms of collaboration, communication, reflection, ethical decision making and professional behaviour during the first three years of medical school (Schripsema et al 2014). These competencies in particular were rated important for the clerkship years by clerkship directors (Windish et al 2004).…”
Section: Participation In Msecasmentioning
confidence: 99%
“…Indeed, another medical school that included puECAs in their procedure concluded that selected students had better skills in terms of collaboration, communication, reflection, ethical decision making and professional behaviour during the first three years of medical school (Schripsema et al 2014). These competencies in particular were rated important for the clerkship years by clerkship directors (Windish et al 2004).…”
Section: Participation In Msecasmentioning
confidence: 99%
“…Una encuesta en Estados Unidos [13] mostró que los estudiantes no reciben una preparación apropiada antes de abordar las rotaciones clínicas formales y necesitan adquirir al menos niveles de comTabla III. Puntuaciones otorgadas por los profesores sobre la actuación de los estudiantes observadores (media ± desviación estándar a ).…”
Section: Curso De Transición Y Rotaciones Precocesunclassified
“…Con o sin curso de transición previo, las rotaciones clínicas precoces se han introducido en los nuevos currículos tanto en su forma llamada 'débil' (contactos ocasionales con pacientes) como de manera formal, con el objetivo de aliviar la ansiedad y mejorar el rendimiento de los estudiantes en las rotaciones formales programadas para el periodo clí-nico [2][3][4][5]13,14]. Diferentes estudios indican que los contactos clínicos precoces motivan y estimulan de diferentes maneras a los estudiantes al mostrarles por vez primera la relevancia práctica de la teoría que aprenden, propulsar su autoconfianza y ayudarles a iniciar el desarrollo de su identidad profesional y las habilidades de relación interpersonal [3,13,14].…”
Section: Administración De La Retroalimentaciónunclassified
See 1 more Smart Citation
“…Recent concerns as to whether medical students are prepared for key competences in their clerkship years [6] may question the validity of medical teaching and exams related to real life. Our model may be seen as a response to a new developing culture of assessment, putting more emphasis on testing clinical skills and performance in the workplace [7,8].…”
Section: External Validitymentioning
confidence: 99%